Āgarā bāzāra : "Nazīra" Akabarābādī kī śāyarī, śaḵẖsīyata, aura unake zamāne para ādhārita sampūrṇa nāṭaka - Tanavīra, Habība (Rādhākr̥shṇa, 1979)
Based on the life and works of Naẓīr Akbarābādi, 1725?-1825? Urdu poet.